The Making, Unmaking and Remaking of Africa’s Independence and Post-Independence Constitutions - Awasom, Nicodemus Fru; Dlamini, Hlengiwe Portia (Philosophy and Politics - Critical Explorations, 2024)
IX, 246 p. 2 illus.